Effects of School‐Based Lifestyle Interventions on Cardiovascular Health in Chinese Children and Adolescents: A Post Hoc Analysis of a National Multicenter Study - Pengfei Guo; Yueqin Zhou; Zhiyong Zou; Yajun Chen; Jin Jing; Yinghua Ma; Yi Song; Wenhua Ling; Jun Ma; Yanna Zhu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We evaluated the effects of a national school‐based lifestyle intervention program against childhood obesity on improving cardiovascular health (CVH), assessed using the recently introduced Life's Essential 8 metric framework. Methods and Results Our post hoc analysis of the national school‐based lifestyle intervention targeting diet and physical activity included 94 schools with eligible students aged 7 to 17 years (intervention group n=30 629; control group n=26 581). We assessed CVH metrics by individual scores for 4 health behaviors (diet, physical activity, nicotine exposure, and body mass index) and 3 health factors (blood lipids, glucose, and pressure). These scores were subsequently combined to calculate the CVH score, health behavior score, and health factor score. The primary outcomes were these 3 composite scores and high CVH (CVH score≥80). All analyses applied a likelihood‐based random‐effects regression modeling following the intention‐to‐treat. The school‐based lifestyle intervention was associated with a 0.89‐point increase in the CVH score (95% CI, 0.03–1.74), 14% greater odds of having high CVH (odds ratio, 1.14 [95% CI, 1.01–1.29]), and a 1.35‐point improvement in the health behavior score (95% CI, 0.32–2.38). According to our subgroup analyses, this intervention had stronger favorable effects on CVH and health behavior scores in primary (grades 1–6) and junior (grades 7–9) schools than in senior high (grades 10–12) schools (P<0.001). Conclusions This school‐based lifestyle intervention improved CVH behaviors in Chinese children and adolescents. The differences in the intervention effect according to school grade imply critical windows for forming healthy lifestyles at younger ages. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02343588.